Study on the Influence of Real Contact Ratio on Gear Meshing Stiffness and Dynamic Response - He Yumin; Hao Anbang (Jixie chuandong)
In order to research the influence of real contact ratio on meshing stiffness and gear dynamic response,the gear meshing assembly model is constructed via the 3 D modeling software SolidWorks,and the model is put into the transient module of FEA software ANSYS Workbench directly,the meshing stiffness under different work conditions is calculated by the Quasi-static method,the influence of real contact ratio on meshing stiffness is studied. Then,under two group operating conditions,the numerical simulations of gear dynamics model with real and theoretical contact ratio is completed respectively by MATLAB,the difference of dynamics response of gear pairs with real and theoretical contact ratio is found. The research shows,during the gear meshing dynamics analysis,the determination of real contact ratio according to special operating condition should be considered,so that obtain a precise analysis resolution.